HUBUNGAN PERILAKU CARING PERAWAT DENGAN KEPUASAN PASIEN DI RUANG RAWAT INAP INTERNA GUNUNG JATIDAN GUNUNG GIRI RSI. SAKINAH MOJOKERTO - puji suryantini, Naning; Chodijah Fahmi, Nur (JURNAL KEPERAWATAN SEHAT, 2014)
Behavior nurse caring represent one the very aspect relate to service treatment, because caring include link between human being and have an effect on to quality service and satisfaction patient. This research aim to know behavioral link nurse caring with satisfaction patient take care to stay with public pain town unit of internal room Sunan Gunung Jati and Sunan Giri RSI. Sakinah Mojokerto . This Research use analytic desaign, sectional cross. Becoming sample is patient internal room Sunan Gunung Jati and Sunan Giri RSI. Sakinah Mojokerto, counted 40 people. Intake sample with technique consecutive sampling. Data collected to through kuisioner structure. Test correlation Spearman used to test behavioralink nurse caring with store satisfaction patient. Result of research indicate that there is significan between behaviour nurse caring with storey satisfaction patient to take care to lodge. Test corelation Spearman showp value = 0,000 < 0,05. Inferential that there is link which is significan between behaviour nurse caring with storey satisfaction patient take care to lodge unit of internal room Sunan Gunung Jati and Sunan Giri RSI. Sakinah MojokertoKeyword : behavioral of nurse, caring and satisfaction patient